Weight regain, but not weight loss, is related to competitive success in real-life mixed martial arts competition - Silveira Coswig, V.; Miarka, B.; Alvarez Pires, D.; Mendes da Silva, L.; Bartel, C.; Boscolo del Vecchio, F. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
We aimed to describe the nutritional and behavioral strategies for rapid weight loss (RWL), investigate the effects of RWL and weight regain in winners and losers, and verify mood state and technical-tactical/time-motion parameters in mixed martial arts. The sample consisted of mixed martial arts athletes after a single real match and was separated into two groups: winners (n = 8; age: 25.4 ± 6.1 years, height: 173.9 ± 0.2 cm, habitual body mass: 89.9 ± 17.3 kg) and losers (n = 7; age: 24.4 ± 6.8 years, height: 178.4 ± 0.9 cm, habitual body mass: 90.8 ± 19.5 kg). Both groups exhibited RWL and weight regain, verified their macronutrient intake, underwent weight and height assessments, and completed two questionnaires (Profile of Mood States and RWL) at (a) 24 hr before weigh-in, (b) weigh-in, (c) postbout, and (d) during a validated time-motion and technical-tactical analysis during the bout. Variance analysis, repeated measures, and a logistic regression analysis were used. The main results showed significant differences between the time points in terms of total caloric intake as well as carbohydrate, protein, and lipid ingestion. Statistical differences in combat analysis were observed between the winners and losers in terms of high-intensity relative time (58 [10-98] s and 32 [1-60] s, respectively), lower limb sequences (3.5 [1.0-7.5] sequences and 1.0 [0.0-1.0] sequences, respectively), and ground and pound actions (2.5 [0.0-4.5] actions and 0.0 [0.0-0.5] actions, respectively), and logistic regression confirmed the importance of high-intensity relative time and lower limb sequences on mixed martial arts performance. RWL and weight regain strategies were related to technical-tactical and time-motion patterns as well as match outcomes. Weight management should be carefully supervised by specialized professionals to reduce health risks and raise competitive performance.